Microfluidic Setup for Simultaneous Separation and Electrochemical Determination of Hg2+ and Ag+ Ions in Water. Issue 3 (12th November 2020) - Di Masi, Sabrina; Laschi, Serena; Pennetta, Antonio; Faraoni, Paola; Ranaldi, Francesco; De Benedetto, Giuseppe Egidio; Malitesta, Cosimino
Abstract: Here is presented a setup made of a combination of an injection valve, a hand‐made chromatographic microcolumn and an electrochemical detector for the simultaneous separation of Hg 2+ and Ag + ions in water. The microcolumns were packed with exchanger resin and used for the separation of Hg 2+ and Ag + ions, whereas a screen‐printed carbon electrode (SPCE) was the amperometric detector. The performances of the SPCE towards ions were firstly studied in a FIA setup. The efficiency of ion separation was then evaluated. The reproducibility, stability, and the regeneration of the obtained microcolumns were also studied and discussed. Abstract :